EKSISTENSI TUHA PEUT DALAM MELAKSANAKAN FUNGSI ANGGARAN DI GAMPONG BABAH KRUENG MANGGIE KECAMATAN PANTON REU KABUPATEN ACEH BARAT - Nila Trisna; Rachmatika Lestari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
Implementation of Gampong Government as contained in Qanun Number 5 of 2003 Chapter 1 General Provisions Article 1 Point 6 is a legal community unit that has the lowest government organization directly under the Mukim, which occupies certain areas led by a keuchik or other name entitled to hold housing matters own stairs. In Points 9 and 10 also mentioned that the government is called the Gampong government is the administration of the gampong government and Tuha Peut Gampong. As for one of the main functions of the Tuha Peut Gampong as contained in Article 31 of Qanun Number 5 of 2003, namely carrying out the Budget Function. Namely the authority to discuss / formulate and approve the draft Village Budget and Revenue and Expenditure (APBG). This research uses normative juridical methods and Empirical Juridical This study uses normative legal research methods, viz. The study refers to the principles, legal concepts, legal norms contained in the Statutory Regulations. The role and responsibilities of the government of Babah Krueng Manggie Village are needed to support all forms of development activities. In practice, the role of Tuha Peut in the budget function has not yet run optimally because members of Tuha Peut do not understand their duties and functions. This is caused by a variety of factors, such as low levels of education as well as the lack of participation of the Tuha Peut Gampong, resulting in a non-optimal implementation of the budget function. Keywords:     Tuha Peut; budget function; Gampong government